INCREASING BASICS OF THE EFFICIENCY OF COMPETITION ACTIVITY AND DEVELOPING TECHNICAL AND TACTICAL PREPARATION - Adilov, Sarvar (Журнал иностранных языков и лингвистики, 2022)
Improving the efficiency of competition activities and developing technical-tactical training, problems and solutions have been explained by literature analysis in the article. It is necessary to solve the current issue through experiments in order to increase the effectiveness of the methods of ensuring that athletes achieve high results in international competitions and improving the technical and tactical preparation of wrestlers during training through a scientific and methodological approach. In the article, it is explained that in different cases of the athlete’s body, which makes it difficult to perform the movements, the method of performing exercises is performed in different ways.